Bibliography of Canadian Bibliographies - Ingles, Ernest, 1948-; Adshead, G. R. (Book collections on Project MUSE., 1994)
This is a completely revised and updated third edition of a standard Canadian reference work that was last published twenty years ago. This new edition has over 7300 entries, with four separate indexes: author, title, English subject, and French subject. In addition, a short-title entry listing provides alternate access to the classified arrangement of the main body of work.Annotation for each entry has been broadened to include: number of entries, if evident; the period or subject, if not evident from the title; a summary of scope; names of compilers, if all are not listed in the main entry; number of pages, volume numbers if applicable; other editions or reprints if any; source title variations if significant; other language titles and form of bilingual presentation; periodicity; and known location.This comprehensive and exhaustive bibliography of published bibliographies will be invaluable to librarians and researchers.